SWOT analysis for development strategy for Silamci natural tourism object facilities in Garut - Sucia, Mentari; Belasunda, Riksa (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Natural tourism contributes significantly to GDP (gross domestic product) and is a major part of the Indonesian economy. In 2022, Indonesia ranked 32nd in the Travel and Tourism Development Index (TTDI), indicating a 3.6 percent rise in the GDP contribution of tourism. The adoption of the